A Multinomial Asymptotic Representation of Zenga's Discrete Index, Its Influence Function and Data-Driven Applications - Kpanzou, Tchilabalo Abozou; Ba, Diam; Da, Gandasor Bonyiri Onesiphore; Lo, Gane Samb (Revstat, 2025)
* In this paper, we consider the Zenga index, one of the most recent inequality indices. We keep the finite-valued original form and address the asymptotic theory. The asymptotic normality is established through a multinomial representation. The influence function is also given. The results are simulated and applied to Senegalese income data. Keywords: * inequality measures; asymptotic behaviour; asymptotic representations; functional empirical process. AMS Subject Classification: * 62G05, 62G20, 62G07, 91B82, 62P20.